2019
DOI: 10.24960/jli.v9i1.5227.9-14
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh jenis pelarut dan kecepatan homogenizer terhadap karakteristik partikel katekin gambir

Abstract: Pengaruh jenis pelarut dan kecepatan homogenizer terhadap karakteristik partikel katekin gambir Effect of solvent type and homogenizer speed on particle characteristics of gambier catechins

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
0
4
0
6
Order By: Relevance
“…It is expressed as the weight average molecular weight divided by the number average molecular weight. Results from the study carried out by Danhier et al [37] (in Yeni et al [38]) states that if the PI value is less than 0.3, it indicates that the From the data in Table 6, it was observed that the addition of SiO 2 to a composite in the right composition caused the z-average or the average size of the particles to become smaller. In addition, the most occurring particle size was observed from the mode value.…”
Section: Characterization Of Particle Size Distribution Of Tio2/sio2 Compositesmentioning
confidence: 98%
“…It is expressed as the weight average molecular weight divided by the number average molecular weight. Results from the study carried out by Danhier et al [37] (in Yeni et al [38]) states that if the PI value is less than 0.3, it indicates that the From the data in Table 6, it was observed that the addition of SiO 2 to a composite in the right composition caused the z-average or the average size of the particles to become smaller. In addition, the most occurring particle size was observed from the mode value.…”
Section: Characterization Of Particle Size Distribution Of Tio2/sio2 Compositesmentioning
confidence: 98%
“…Ukuran formulasi yang kecil menunjukkan emulsi yang baik antara formulasi dalam air. Pegecilan ukuran dengan menggunakan homogizer dan sonikasi mampu meningkatkan homogenisasi dan pembentukan emulsi yang lebih seragam dibandingkan sebelum pengecilan ukuran [24]. Hasil penelitian juga menunjukkan semakin lama sonikasi dilakukan, maka ukuran partikel juga semakin kecil.…”
Section: Gambarunclassified
“…Teknologi proses dilakukan berdasarkan perbedaan sifat kelarutan antara katekin dan tanin dalam air. Katekin dalam keadaan murni sulit larut dalam air dingin, mudah larut dalam air panas, larut dalam alkohol dan etil asetat (Yeni et al, 2019).…”
Section: Kabupaten Limapuluhunclassified
“…Teknologi proses ekstraksi untuk mendapatkan katekin dengan kandungan yang diharapkan dapat dilakukan melalui ekstraksi lanjutan gambir hasil pencucian ulang dengan air (gambir murni). Penelitian peningkatan kemurnian katekin dari gambir murni sudah dilakukan, yaitu menggunakan kolom amberlit dengan campuran pelarut etanol dan etilasetat, tetapi katekin yang dihasilkan berwarna kurang cerah (Muchtar et al, 2008, Yeni et al, 2019, 2014a.…”
Section: Kabupaten Limapuluhunclassified